Architectural Design of Self‐Assembled Hollow Superstructures. Issue 38 (5th September 2018) - Xue, Zhenjie; Wang, Peilong; Peng, Aidong; Wang, Tie
Abstract: Colloidal nanoparticle assemblies are widely designed and fabricated via various building blocks to enhance their intrinsic properties and potential applications. Self‐assembled hollow superstructures have been a focal point in nanotechnology for several decades and are likely to remain so for the foreseeable future. The novel properties of self‐assembled hollow superstructures stem from their effective spatial utilization. As such, a comprehensive appreciation of the interactive forces at play among individual building blocks is a prerequisite for designing and managing the self‐assembly process, toward the fabrication of optimal hollow nanoproducts. Herein, the emerging approaches to the fabrication of self‐assembled hollow superstructures, including hard‐templated, soft‐templated, self‐templated, and template‐free methods, are classified and discussed. The corresponding reinforcement mechanisms, such as strong ligand interaction strategies and extra‐capping strategies, are discussed in detail. Finally, possible future directions for the construction of multifunctional hollow superstructures with highly efficient catalytic reaction systems and an integration platform for bioapplications are discussed. Abstract : Self‐assembled hollow superstructures have received tremendous attention owing to their structural superiority and intrinsic enhanced properties, suited to various applications in material science and bioscience. Fabrication methods and reinforcement mechanisms for achieving stable hollow shells are reviewed. Anticipated designs for multifunctional hollow superstructures and future research directions for the development of hollow superstructures are also discussed.